1985
DOI: 10.1002/ijc.2910360104
|View full text |Cite
|
Sign up to set email alerts
|

The value of HLA phenotypes in the prognosis of Hodgkin's lymphoma

Abstract: The study included 52 patients with Hodgkin's disease, 32 males and 20 females, whose ages ranged from 3 to 36 years (34 under and 18 over 15 years). All patients were carefully staged, and lymph-node biopsies were taken for histopathological examination. HLA phenotype determinations were carried out, and the frequencies were statistically compared with those of normal Egyptian controls. We followed the patients for 3 years to monitor the effect of therapy. In order to determine the prognostic value of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
1
7
2
Order By: Relevance
“…Moreover, individuals homozygous for HLA-A*01 are also homozygous for the risk alleles of the 2 SNPs flanking the associated haplotype (rs2530388 and rs6457110) as observed in our previous study. Together, these data confirm the results of this study that patients with EBV ϩ HL are significantly more often homozygous for 33 The relative risk showed that persons carrying HLA-A*01 were 6 times more susceptible than those lacking it. These data were supported by Falk and Osoba, who also reported an increased incidence of HLA-A*01 in Canadian patients with HL.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, individuals homozygous for HLA-A*01 are also homozygous for the risk alleles of the 2 SNPs flanking the associated haplotype (rs2530388 and rs6457110) as observed in our previous study. Together, these data confirm the results of this study that patients with EBV ϩ HL are significantly more often homozygous for 33 The relative risk showed that persons carrying HLA-A*01 were 6 times more susceptible than those lacking it. These data were supported by Falk and Osoba, who also reported an increased incidence of HLA-A*01 in Canadian patients with HL.…”
Section: Discussionsupporting
confidence: 89%
“…An association with HLA-DR5 has been reported previously by Robertson et al in familial cHL. 31 Significant effects of HLA-A1, HLA-B8, and HLA-B18 for cHL that have been reported in previous publications [12][13][14] could not be confirmed in the total patient group in our study, whereas the previously reported association with HLA-B5 29 was borderline significant in the overall cHL group in our study. These differences might be explained by differences in sample size, patient selection, and proportion of EBV ϩ cases.…”
Section: R E T R a C T E Dcontrasting
confidence: 81%
“…6,[12][13][14] More recently, we focused on the EBV ϩ cHL subgroup in a genetic screening study of the entire HLA region. 5 In a subsequent fine-screening analysis, we found a strong association of specific HLA-A alleles with susceptibility to EBV ϩ cHL in Dutch and English patients.…”
Section: Introductionmentioning
confidence: 99%
“…The HLA-B5 association has been reported previously [35]. Significant effects of HLA-A1, HLA-B8, HLA-B18 and HLA-DR5 for cHL that have been reported in previous publications [12][14], [36] could not be confirmed in the total patient group in our study. These differences might be explained by differences in sample size, patient selection, and proportion of EBV+ cases, since we found HLA-A1 specifically in EBV+ cHL an HLA-DR5 specifically in EBV− cHL.…”
Section: Discussioncontrasting
confidence: 50%
“…Initial HLA association studies in cHL were performed without taking EBV status into account and associations of HLA-A1, HLA-B5, HLA-B8 and HLA-B18 with cHL have been described, although the degree of reproducibility was low [6], [12][14]. More recently, we focused on EBV stratified cHL subgroups in a genetic screening study of the entire HLA region [5].…”
Section: Introductionmentioning
confidence: 99%